SOSIALISASI, PELATIHAN DAN PENDAMPINGAN PENGOLAHAN SAMPAH DI PESANTREN AL FATH TALANG KERAMAT MENUJU PESANTREN YANG BERWAWASAN LINGKUNGAN - Eka Sri Yusmartini; Sri Parwanti; Mardwita Mardwita (Jurnal Abdi Insani, 2022)
Garbage is part of life on this earth and the amount is increasing along with increased human activity. The amount of waste disposed of in landfills is increasing as human activities increase. Al Fath Talang Keramat Islamic Boarding School in Banyuasin Regency, South Sumatra is one of the educational facilities which has 118 students, with a total of 17 administrators. This Islamic boarding school already has good environmental management but there has been no effort to reduce the amount of waste that will be taken to the TPA. The purpose of this community service activity is to make the Islamic boarding school environment more environmentally sound towards Green Islamic Boarding Schools by involving students and Islamic boarding school caretakers (partners) as actors. Partners will have the ability to sort and manage waste and are expected to have economic value and be sustainable. The service method is carried out in several stages. The implementation stage begins with outreach to partners. The next stage is to conduct waste sorting training based on the types of organic and inorganic waste. Furthermore, training on making invitation words is carried out. The mentoring method is carried out for students who have attended socialization and training as many as 10 students. This community service activity has had an impact on knowledge and behavior change for students and pesantren administrators. Partners have acquired skills in sorting and processing organic and inorganic waste, and making waste of economic value. This can be seen from the results of evaluations with partners, who previously did not know anything about the problem of waste management, and after the activities were able to properly manage waste in the pesantren environment. This has an impact on the pesantren environment which will slowly move towards green pesantren as expected. Based on these results, it can be concluded that the service activities carried out by the PKM team have been carried out well.